(untitled) (Revista Internacional de Folkcomunicação, 2021)
This article presents a survey on the realization of audiovisual events held in virtual mode, due to the Covid-19 pandemic. The cutout refers to the Brazilian context, more specifically to cultural projects based in cities in Minas Gerais, in 2020. The main data collection technique used was the availability of a virtual form, containing open and closed questions. Seven of the eleven cultural projects selected for the sample participated in the study. The findings can be related to three fronts: (1) challenges of adapting all the programming idealized for the face-to-face format and offered in the virtual modality; (2) remote access gains from new audiences; (3) trend towards future editions in a hybrid format.